Trauma Awareness Training for Psychology Students of Nusa Cendana University - Eduardus J. Angga Huky; Manafe, Rizky Pradita; Cheveline E.da Costa; Benu, Juliana Marlin Y. (Fakultas Psikologi Universitas Pancasila, 2025)
Traumatic experience is a crisis that suppresses the psychological condition of individuals in response to an event. Individuals who have experienced traumatic events often experience various psychological pressures, such as stress, depression, and anxiety. One strategy to help trauma survivors deal with this condition is to provide trauma awareness training. This training is useful for individuals to realize traumatic experiences within themselves and to help other individuals in the community. The methods in this training are lectures and experiential learning to involve 23 psychology students at Nusa Cendana University. The results of the training showed that psychology students at Nusa Cendana University experienced an increase in knowledge about trauma awareness, with a pre-test score of 75.6 to 90.9 for the post-test score.